Optimization of a Process to Obtain Selenium-Enriched Freeze-Dried Broccoli with High Antioxidant Properties - Reyes-Salinas, A; Mahn-Osses, A; Barrientos-Carvacho, H; Barrientos-Carvacho, H (2012)
Broccoli exhibits a high content of antioxidant and anticarcinogenic compounds, such as polyphenols and selenium. Since it is mostly consumed as a processed food, elucidating the processing conditions that minimize nutritional losses becomes relevant. The process composed of a blanching step followed by freeze-drying of selenium-enriched broccoli was optimized, in order to maximize the content of Se-methyl selenocysteine (SMSeC), total polyphenols content and anti-radical power (ARP). The optimal blanching conditions agreed for the three responses, and were immersion in water at 72 °C during 1 min. The optimal freeze-drying conditions were slow freezing rate, atmospheric pressure (96.13 kPa), and application of infrared radiation (IR). These conditions allowed keeping 25% ARP, 18% polyphenols content and 174% SMSeC compared to the fresh vegetable. These results will help in establishing the most adequate processing conditions that allow keeping the functional properties of broccoli as a processed food. © 2012 Elsevier Ltd.